THE Effect of Institutional Ownership and Executive Compensation on Company Performance (Study on Food and Beverage Industry Listed in Indonesia Stock Exchange From 2014-2018) - Yunita Riaswati; Suherman; Umi Mardiyati (JURNAL DINAMIKA MANAJEMEN DAN BISNIS, 2021)
ABSTRACT The purpose of this study is to determine the effect of institutional ownership and executive compensation on company performance in the food and beverage industry listed on the Indonesia Stock Exchange from 2014-2018. The variables used in this study are institutional ownership and executive compensation as independent variables, company performance (proxied by Tobin's Q, ROA, and ROE) as the dependent variable, as well as company size, leverage (proxied by DAR), and company age as the dependent variable. . This study uses annual report data and financial statements of food and beverage sub-sector companies listed on the Indonesia Stock Exchange in the 2014-2018 period. The sampling method used was the purposive sampling method, using balanced panel data as a method of data analysis. The results of this study indicate that institutional ownership has a significant positive effect on company performance (on Tobin's Q proxy) and insignificant (on the proxy of ROA and ROE), and executive compensation does not have a significant effect on company performance.